MHD mixed convection boundary layer flow toward a stagnation point on a vertical surface with induced magnetic field. - Md.Ali, Fadzilah; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (2011)
In this paper, the steady magnetohydrodynamic (MHD) mixed convection stagnation point ﬂow of an incompressible, viscous, and electrically conducting ﬂuid over a vertical ﬂat plate is investigated. The effect of induced magnetic ﬁeld is taken into account. Numerical results are obtained using an implicit ﬁnite-difference scheme. Both assisting and opposing ﬂows are considered. The results for skin friction, heat transfer, and induced magnetic ﬁeld coefﬁcients are obtained and discussed for various parameters. The velocity, temperature, and induced magnetic ﬁeld proﬁles are also presented. For the case of the opposing ﬂow, it is found that dual solutions exist for a certain range of the buoyancy parameter. Dual solutions are also obtained for the assisting ﬂow.